Network Security Intelligence for Small and Medium Scale Industry 4.0: Design and Implementation (Global Journal of Computer Science and Technology, 2018)
The development of Internet of Things (IOT) technology became one of the proponents in the industrial revolution 4.0. Digital transformation began to be applied to the entire manufacturing industry, services, transportation and education which have slowly shifted utilizing IOT technology. The industrial revolution 4.0 has an impact on digital transformation and becomes a necessity that can change business patterns such as the ease of data interaction services between industries to customers that are also supported by ease of access and speed of decision making. However, in its development, stakeholders tend to focus on infrastructure and information systems, while the security of information systems is still a comfort zone for industries in the transformation to industry 4.0. The issue of information system security will be a challenge for the industry with open access to information systems, otherwise focus will hamper the business process of the industry. In this research will be discussed about the modeling and implementation of information system security with a combination of web-based security methods with port knocking firewall model and short message service gateway as a security medium with the concept of ease of access with safe and comfortable. The result of this research has been testing penetration testing using network tools.
Keywords: industry 40; cyber security; port knocking; short message service gateway